Know your limits! (IV)

Calculus Level 3

Evaluate lim x 1 x 1 / 2 ( 2 x ) 1 / 3 x 2 + x 2 . \lim_{x\rightarrow1} \frac{x^{1/2}-(2-x)^{1/3}}{x^2+x-2} . If your answer can be expressed as a b \dfrac{a}{b} where a a and b b are coprime positive integers, find the value of a + b a+b .


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Noel Lo
Nov 29, 2015

Applying L'Hopital's rule, lim x 1 x 1 / 2 ( 2 x ) 1 / 3 x 2 + x 2 = lim x 1 1 2 x 1 / 2 ( 1 ) 1 3 ( 2 x ) 2 / 3 2 x + 1 = lim x 1 1 2 x 1 / 2 + 1 3 ( 2 x ) 2 / 3 2 x + 1 \lim_{x\rightarrow1} \frac{x^{1/2}-(2-x)^{1/3}}{x^2+x-2} =\lim_{x\rightarrow1} \frac{\frac{1}{2}x^{-1/2}-(-1)\frac{1}{3}(2-x)^{-2/3}}{2x+1} = \lim_{x\rightarrow1} \frac{\frac{1}{2}x^{-1/2}+\frac{1}{3}(2-x)^{-2/3}}{2x+1}
= 1 2 + 1 3 2 + 1 = 5 6 3 = 5 18 =\frac{\frac{1}{2}+\frac{1}{3}}{2+1}= \frac{\frac{5}{6}}{3}=\frac{5}{18}

So a=5 and b=18. a + b = 23 a+b =\boxed{23}

Armain Labeeb
Jul 10, 2016

lim x 1 x 1 / 2 ( 2 x ) 1 / 3 x 2 + x 2 = lim x 1 ( x 2 x 3 x 2 + x 2 ) A p p l y i n g L H o p i t a l s R u l e = lim x 1 ( 1 2 x + 1 3 ( x + 2 ) 2 3 2 x + 1 ) = lim x 1 ( 3 ( 2 x ) 2 3 + 2 x 6 ( 2 x ) 2 3 x ( 2 x + 1 ) ) P l u g i n V a l u e s = 3 ( 2 1 ) 2 3 + 2 1 6 ( 2 1 ) 2 3 1 ( 2 1 + 1 ) a b = 5 18 a + b = 5 + 18 = 23 \begin{aligned} \lim _{ x\to 1 } \frac { x^{ 1/2 }-(2-x)^{ 1/3 } }{ x^{ 2 }+x-2 } & =\lim _{ x\to \: 1 } \left( \frac { \sqrt { x } -\sqrt [ 3 ]{ 2-x } }{ x^{ 2 }+x-2 } \right) & \\ Applying\quad L'Hopital's\quad Rule & =\lim _{ x\to \: 1 } \left( \frac { \frac { 1 }{ 2\sqrt { x } } +\frac { 1 }{ 3\left( -x+2 \right) ^{ \frac { 2 }{ 3 } } } }{ 2x+1 } \right) & \\ & =\lim _{ x\to \: 1 } \left( \frac { 3\left( 2-x \right) ^{ \frac { 2 }{ 3 } }+2\sqrt { x } }{ 6\left( 2-x \right) ^{ \frac { 2 }{ 3 } }\sqrt { x } \left( 2x+1 \right) } \right) & \\ Plug\quad in\quad Values & =\frac { 3\left( 2-1 \right) ^{ \frac { 2 }{ 3 } }+2\cdot \sqrt { 1 } }{ 6\left( 2-1 \right) ^{ \frac { 2 }{ 3 } }\sqrt { 1 } \left( 2\cdot \: 1+1 \right) } & \\ \therefore \frac { a }{ b } & =\frac { 5 }{ 18 } & \\ \Longrightarrow a+b & =5+18 & \\ & =23 & \end{aligned}

Ramiel To-ong
Dec 8, 2015

nice problem

Thank you!

Noel Lo - 5 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...